Effect of Fruit Maturation on Germination and Vigour of Bakul (Mimusops elengi Linn) Seeds - Bahar, Nawa (Indian Forester, 2016)
Mimusops elengi is an evergreen tree species belonging to family Sapotaceae with several uses as source of oil, fodder, fuel wood, timber and medicine. It is locally known as Bakul. Seeds were collected from the green, green yellow and yellow fruit to assess the best maturation period. All the characters such as germination per cent (72.65%), mean germination time (17.40), germination value (9.00) germination energy (4.23), root length(5.28cm), shoot length (3.75cm) and seedling vigour index ( 656.03) were found more in seed obtained, from yellow fruit as compare to green and green yellow.